Principles of superconductive devices and circuits - Van Duzer, Theodore (Prentice Hall, 1999)
Aimed at first-year electrical engineering and physics courses at the graduate level, this book introduces theories useful for practical analysis, providing an understanding and the basis for a variety of applications.